Faktor Determinan Financial Statement Fraud: Pengujian Kualitas Audit sebagai Pemoderasi - Sindi Tiastuti; Sri Wahyuni; Azmi Fitriati; Hardiyanto Wibowo (Transpublika Publisher, 2025)
This study aims to determine the effect of financial target, profitability, audit committee, and institutional ownership on financial statement fraud with audit quality as moderation. This study uses a quantitative approach with secondary data. The population in this study are consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2022-2023. The sample selection used a purposive sampling method and obtained 104 data samples. The analysis technique used in this study is multiple regression analysis with moderated regression analysis (MRA) by SPSS version 26 program. The results showed that financial target has a positive effect on financial statement fraud, profitability has a negative effect on financial statement fraud, audit committee and institutional ownership have no effect on financial statement fraud, audit quality is proven can moderate by strengthening the effect of financial target on financial statement fraud, audit quality is not proven can moderate the effect of profitability, audit committee, and institutional ownershipon financial statement fraud.